A comprehensive study on shape memory behavior of PEG plasticized PLA/TPU bio-blends. (5th January 2020) - Boyacioglu, S.; Kodal, M.; Ozkoc, G.
Graphical abstract: Highlights: The shape recovery ratios increased with increasing TPU content in the blends. The decreasing molecular weight of PEG maximized the shape recovery values. The maximum total recovery was obtained at 60 °C for 20/80 PLA/TPU blends. The shape recovery ratios improved from 45% to over 65–70% at 45 °C. Plasticized PLA and TPU were non-toxic and safe to use in-vivo conditions. Abstract: In this study, the shape memory behavior of poly(ethylene glycol) (PEG) plasticized poly(lactic acid)/thermoplastic polyurethane (PLA/TPU) blends was investigated as functions of PLA/TPU ratio, plasticizer molecular weight and programming conditions. The mechanical, thermal and morphological properties of polymer blends were characterized by tensile tests, differential scanning calorimeter (DSC) and scanning electron microscopy (SEM). It was found that the addition of plasticizers decreased the glass transition and cold crystallization temperature of PLA phase. As the molecular weight of PEG increased, the plasticization efficiency decreased. The shape memory tests showed that the higher the TPU content, the higher the recovery ratio between 40 °C and 55 °C temperatures ranges. The maximum total recovery was obtained at 60 °C for 20/80 PLA/TPU blends. The decreasing molecular weight of PEG maximized the shape recovery values. It was demonstrated that the samples were able to lift stresses up to 245 kPa during shape recovery depending on the temperature and composition. Moreover, the biocompatibility and cytotoxicity tests revealed that plasticized PLA/TPU blends are non-toxic and safe to use in-vivo conditions.